2015
DOI: 10.1097/mbc.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

An automated method for fibrin clot permeability assessment

Abstract: The fibrin clot permeability coefficient (Ks) is a useful measure of porosity of the fibrin network, which is determined by a number of genetic and environmental factors. Currently available methods to evaluate Ks are time-consuming, require constant supervision and provide only one parameter. We present an automated method in which drops are weighed individually, buffer is dosed by the pump and well defined clot washing is controlled by the software. The presence of a straight association between drop mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…32 Recently, we have developed and reported on an automated method for K s assessment, in which drops are weighed individually, buffer is dosed by a peristaltic pump, and welldefined clot washing is controlled by dedicated software. 33 A close association between drop mass and dripping time after proper clot washing allowed to shorten the measurement time. 33 Collet et al investigated clots generated from platelet-rich and platelet-poor plasma in thin glass microchambers (250 µm).…”
Section: Assays To Measure Fibrin Clot Permeabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…32 Recently, we have developed and reported on an automated method for K s assessment, in which drops are weighed individually, buffer is dosed by a peristaltic pump, and welldefined clot washing is controlled by dedicated software. 33 A close association between drop mass and dripping time after proper clot washing allowed to shorten the measurement time. 33 Collet et al investigated clots generated from platelet-rich and platelet-poor plasma in thin glass microchambers (250 µm).…”
Section: Assays To Measure Fibrin Clot Permeabilitymentioning
confidence: 99%
“…33 A close association between drop mass and dripping time after proper clot washing allowed to shorten the measurement time. 33 Collet et al investigated clots generated from platelet-rich and platelet-poor plasma in thin glass microchambers (250 µm). 34 Using this approach, they showed that platelets modify fibrin clot structure leading to a 3.5-fold increased K s .…”
Section: Assays To Measure Fibrin Clot Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of standardised approach to fibrin clot structure assessment and permeability studies limits reproducibility and usefulness [ 43 ]. However, the possibility of an automated system might allow this technique to be used more widely [ 115 ].…”
Section: Current Situation Limitations and Future Directionsmentioning
confidence: 99%